2021
DOI: 10.1186/s12955-021-01819-4
|View full text |Cite|
|
Sign up to set email alerts
|

Family reported outcomes, an unmet need in the management of a patient's disease: appraisal of the literature

Abstract: Background A person’s chronic health condition or disability can have a huge impact on the quality of life (QoL) of the whole family, but this important impact is often ignored. This literature review aims to understand the impact of patients' disease on family members across all medical specialities, and appraise existing generic and disease-specific family quality of life (QoL) measures. Methods The databases Medline, EMBASE, CINHAL, ASSIA, PsycI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 150 publications
1
17
0
Order By: Relevance
“…The study also confirmed that disability is a personal event and a family event (Shah et al, 2021) and revealed a negative correlation between DS and FF, which is consistent with the relationship found in the study of poststroke patients (Yang et al, 2021). In the present study, 52.5% of families are lineal families whose adult males usually work outside and act as the core family members.…”
Section: Discussionsupporting
confidence: 92%
“…The study also confirmed that disability is a personal event and a family event (Shah et al, 2021) and revealed a negative correlation between DS and FF, which is consistent with the relationship found in the study of poststroke patients (Yang et al, 2021). In the present study, 52.5% of families are lineal families whose adult males usually work outside and act as the core family members.…”
Section: Discussionsupporting
confidence: 92%
“…Several instruments have been developed to assess the impact of a person's health condition/ disability on family members/partners to understand this secondary and often unrecognised burden of disease. 19 Although the reliability and validity of several FQoL instruments have been established, they are not yet accepted in clinical practice. The assessment of the meaning of scores of an instrument and the practicality of its use in a clinical setting are more important than just Open access meeting conventional psychometric requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The original article [ 1 ] contained several typos which were mistakenly incorporated by the production team that handled this article.…”
Section: Correction To: Health Qual Life Outcomes (2021) 19:194 Https://doiorg/101186/s12955-021-01819-4mentioning
confidence: 99%